2003
DOI: 10.1029/2002ja009592
|View full text |Cite
|
Sign up to set email alerts
|

Plasma density enhancements associated with equatorial spread F: ROCSAT‐1 and DMSP observations

Abstract: [1] Large-scale plasma density depletions are typically associated with equatorial spread F (ESF) plasma irregularities in the nightside F region, especially in the postsunset sector. Data gathered on the ROCSAT-1 spacecraft reveal numerous cases of localized, discrete plasma density enhancements in the nightside low-latitude region at $600 km altitude. In some cases, nearly simultaneous DMSP observations at $800 km reveal similar density enhancements in the same local time sector. These density enhancement st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

22
160
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 90 publications
(184 citation statements)
references
References 22 publications
22
160
1
Order By: Relevance
“…The ion density data given by Kil and Heelis (1998) also reveals a number of ion density enhancements along with the depletions in the ion density. But they did not emphasize these enhancements, as has been pointed out by Le et al (2003). Recently, Le et al (2003) have reported localized regions of enhancements in the ion density, occurring with or without the plasma density depletions.…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…The ion density data given by Kil and Heelis (1998) also reveals a number of ion density enhancements along with the depletions in the ion density. But they did not emphasize these enhancements, as has been pointed out by Le et al (2003). Recently, Le et al (2003) have reported localized regions of enhancements in the ion density, occurring with or without the plasma density depletions.…”
Section: Discussionmentioning
confidence: 92%
“…The plasma density enhancements observed by Oya et al (1986), Kil and Heelis (1998) and Le et al (2003) also could not be compared with those observed with the ATS series satellites. The observations of Oya et al (1986), Kil and Heelis (1998) and Le et al (2003) are based on the instruments on board the satellites that had a circular orbit (650 km for Hintori, 370 km and 400 km for AE-E, 600 km for ROC-SAT and 850 km for DMSP satellite).…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations